Application of Discrete Event Simulation (DES) for Queuing System Improvement at Hypermarket - Mohamad, Fazeeda; Filza Saharin, Siti (KnE Social Sciences, 2019)
This paper focuses on the development of a computer simulation model for improving the queuing system at a hypermarket using Discrete Event Simulation (DES) and to propose the most efficient hypermarket queuing system for overall improvement. Data were collected from the Hypermarket A using the time study. The method of this study is using modeling and simulation. Arena Simulation Software is used to develop the model to replicate the actual system. Three scenarios had been tested, and the alternatives will be ranked based on the level of the efficiency of the system performance. The most efficient queuing system is identified based on the scenario analysis. In this study, the waiting time for each customer can be improved by up to 26%, which equivalent to 5.24 minutes. Overall, this study contributes to a better understanding of the queuing system performance. Keywords: hypermarket, queuing system, waiting time, simulation, Discrete Event Simulation (DES).